The expression of apoptosis related genes in HK-2 cells overexpressing PPM1K was determined by RNA-seq analysis - Zhang, Li; Sang, Xiaohong; Han, Yuanyuan; Abulitibu, Alpati; Elken, Mufunayi; Mao, Zhijie; Kang, Shaotao; Yang, Wenjun; Lu, Chen (Frontiers in Genetics, 2022)
Abstract Chronic kidney disease (CKD) is a serious disease that endangers human health. It is reported that inhibiting renal cell apoptosis can delay the progress of CKD. Our previous study found that the mice with protein phosphatase Mg2+/Mn2+ dependent 1K (PPM1K) gene deletion had obvious symptoms of glomerular vascular and interstitial vascular dilatation, congestion and hemorrhage, glomerular hemorrhage and necrosis, interstitial fibrous tissue proliferation, decreased urinary creatinine clearance, and increased urinary protein level. In addition, studies have found that PPM1K is essential for cell survival, apoptosis and metabolism. However, no study has confirmed that PPM1K can inhibit renal cell apoptosis. In this study, PPM1K was overexpressed in human kidney-2 cells (HK-2), and the biological process of differentially expressed genes and its effect on apoptosis were comprehensively screened by RNA sequencing (RNA-seq). Through sequencing analysis, we found that there were 796 differentially expressed genes in human renal tubular epithelial cells transfected with PPM1K gene, of which 553 were down-regulated and 243 were up-regulated. Enrichment analysis found that differentially expressed genes may play an important role in amino acid metabolism and biosynthesis. In the list of functional pathways by GO analysis, we also found G0S2、GADD45A、TRIB3、VEGFA、NUPR1、IL-6、MAGED1、CCL2、TP53INP1 and other genes can be enriched in apoptosis related pathways. Further screening by quantitative real-time PCR showed that G0S2、IL-6、TP53INP1、NUPR1 and others may be involved in PPM1K induced apoptosis of HK-2 cells. In conclusion, these findings provide some data support for the study of HK-2 cell apoptosis mechanism, and also provide a scientific theoretical basis for further study of the effect of PPM1K on kidney disease.